The Competitiveness of Indonesian Crude Palm Oil in International Market - Daeng Ahmad Fakhrian Zuhdi; Muhammad Faisyal Abdullah; Muhammad Sri Wahyudi Suliswanto; Setyo Tri Wahyudi (Department of Development Economics, Universitas Sriwijaya, 2021)
The purpose of this study was to know the competitiveness of Indonesia’s CPO exports in the world and strategies to increase Indonesia’s CPO competitiveness. The required data is secondary data from the report of CPO export in Indonesia in 1993-2017. This research-based on the background by the issue of palm oil discrimination by the European Union, where Europe is one of Indonesia’s main CPO export destinations. This research uses a qualitative-quantitative approach, analysis with a quantitative approach is used to analyze the comparative advantage of Indonesia’s palm oil in the international market used RCA. Analysis with a qualitative approach is used to analyze which strategies will be used to improve the competitiveness of Indonesian palm oil. The results of the study show that in 2017 export performance of Indonesia’s palm oil increased. It showed by the value of RCA>1 which is 55,47 and an average of 37,22, Indonesia has the competitiveness of palm oil because of the increased export volume of palm oil to the major importer countries, such as India, Pakistan, and Europe. Indonesia’s still competitive in Europe and Asia’s market based on the average value of the RCA index.